Kontribusi Pemulung dalam Pengelolaan Sampah Berkelanjutan : Studi Kasus TPA Karangdieng Mojokerto - Elvina Nuzu Fazhitya (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
The increasing population and human activities have significantly contributed to the rise in waste volume across Indonesia, including in Mojokerto Regency. One of the areas facing this challenge is the Karangdieng Final Processing Site (TPA) in Kutorejo District. In the midst of limited infrastructure and the lack of effective formal policies, waste pickers emerge as key social actors who contribute to waste reduction through the sorting of recyclable materials. This study aims to examine the involvement of waste pickers in waste management at the Karangdieng landfill and to identify the challenges they face in their daily activities. A qualitative research approach was employed, using purposive sampling to select four waste pickers and one landfill worker as informants. Data were collected through in-depth interviews, participatory observations, and documentation, and were analyzed descriptively by applying the symbolic interactionism perspective. The findings reveal that waste pickers play a significant role in reducing waste accumulation and supporting recycling practices while also fostering social solidarity within their community. However, they encounter various challenges, including low and unstable income, occupational health and safety risks, polluted working environments, and limited access to social protection and basic services.